Solanum tuberosum- An Appealing Alternative for Solanesol - Sharma, Manish (International Journal of Pharmaceutical & Biological Archive, 2010)
Highly purified Solanesol is well-sold raw material. It is found that highly purified Solanesol itself can be used either as a drug or intermediate. It is mainly used in synthesis of anticancer compounds, CoQ10 and vitamin K2. At present the market rate of Solanesol is around 300 per Kg. So the promise of reduced cost and bulk production makes S. tuberosum an appealing alternative for extraction of Solanesol.